2nd Floor Budget Planning Assistance (RAB) at Nurul Iman mosque, Bahari Tiga Village - Abdu, Muhammad (Room of Civil Society Development, 2023)
This research aims to assist the analysis of the cost budget for the continuation of the construction of the 2nd floor of the nurul iman mosque of the third nautical village so that in determining the amount of costs, material needs can be known in more detail so as to minimize the risk of spending overruns in the use of the budget. In determining costs, the analysis is calculated based on the planned work drawings. With a total budget of four hundred and fifty-four million.